2010
DOI: 10.4028/www.scientific.net/amr.152-153.1115
|View full text |Cite
|
Sign up to set email alerts
|

The Stress Concentration Factor of Different Corrosion Pits Shape

Abstract: The stress concentration effect of different corrosion pits is different, the shapes of corrosion pits can be seen as semi-ellipsoidal, the short half axes、long half axes and depth of corrosion are 、 and , through finite element analyze, we can see that the stress concentration factors increase with the increase of , but the stress concentration factors decrease with the increase of .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Many researchers have utilized FEA to study the pit‐to‐crack transition in different alloys, but to date, all studies have been limited to static loading only. In the present study, to consider the effect of cyclic loading and local plastic deformation, 3D elastic‐plastic FEA has been carried out using ABAQUS software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have utilized FEA to study the pit‐to‐crack transition in different alloys, but to date, all studies have been limited to static loading only. In the present study, to consider the effect of cyclic loading and local plastic deformation, 3D elastic‐plastic FEA has been carried out using ABAQUS software.…”
Section: Methodsmentioning
confidence: 99%
“…The pit geometries used for FEA modeling here are similar in terms of aspect ratio to those generated during experiments. Previous studies have used FEA to study the pit‐to‐crack transition under static loading using the elastic and elastic‐plastic material models . Other than a study by some of the authors of the present work, we are not aware of any other published data on FEA of corrosion pits under cyclic loading in air or in saline environment.…”
Section: Introductionmentioning
confidence: 96%
“…1 Pit-to-crack transitions under static loading have been investigated numerically and experimentally in previous studies. 4,[16][17][18][19][20][21][22][23][24] However, in spite of the importance of cyclic loading in reducing the life of components, the variation of local stress around corrosion pits under fatigue loading and its influence on fatigue life prediction have not been established. This issue constitutes a significant knowledge gap in the understanding of the pit-to-fatigue crack transition process.…”
Section: Introductionmentioning
confidence: 99%
“…As some authors [24,25] confirmed recently, the stress concentration of pits increased with the pit aspect ratio (depth-diameter ratio). Consequently, significant stress concentration would form in the needle-like pit under tensile stress.…”
Section: Discussionmentioning
confidence: 60%